Current Status and Progress of Research on Oil and Gas Pipeline Failure Analysis - Liu, Wanfu; Xiong, Xiao; He, Xun (Scientific Journal of Technology, 2026)
With the development of social economy, the service mileage of oil and gas pipelines is increasing, and their service life is gradually extending. This article analyzes the types of pipeline failures and their solutions, including third-party mechanical damage, corrosion damage (external and internal corrosion), and the impact of natural disasters on pipeline safety. These issues directly threaten the stability and safety of pipeline operations. In terms of key technologies, it details the application of real-time monitoring technology, anti-corrosion coating technology, advanced materials, and new non-destructive testing technologies. These technologies are crucial for enhancing the stability and safety of pipeline operations.